Five‐year efficacy and safety of tildrakizumab in patients with moderate‐to‐severe psoriasis who respond at week 28: pooled analyses of two randomized phase III clinical trials (reSURFACE 1 and reSURFACE 2). (1st August 2021) - Thaci, D.; Piaserico, S.; Warren, R.B.; Gupta, A.K.; Cantrell, W.; Draelos, Z.; Foley, P.; Igarashi, A.; Langley, R.G.; Asahina, A.; Young, M.; Falqués, M.; et al.
Summary: Background: The phase III reSURFACE 1 and reSURFACE 2 (NCT01722331/NCT01729754) trials of the anti‐interleukin‐23p19 monoclonal antibody tildrakizumab (TIL) for psoriasis treatment are complete. Objectives: We present 5‐year pooled data from reSURFACE 1 and reSURFACE 2. Methods: reSURFACE 1 and reSURFACE 2 were double‐blind, randomized, controlled studies with optional long‐term extensions. Adults with moderate‐to‐severe chronic plaque psoriasis were randomized 2 : 2 : 1 to TIL 100 mg (TIL 100) or 200 mg (TIL 200) or placebo at weeks 0 and 4, and every 12 weeks thereafter [reSURFACE 2 included an etanercept (ETN) arm]. Efficacy outcomes included proportions of patients achieving absolute and relative improvement from baseline Psoriasis Area and Severity Index (PASI) score through week 244 in TIL responders (≥ 75% improvement from baseline PASI; PASI 75 response) continuously receiving the same dose and ETN partial responders and nonresponders (PASI < 75 response) switched to TIL 200 at week 28. Safety was assessed from adverse events (AEs) in all patients as treated. Results: Efficacy analyses included 329 and 227 week 28 responders to TIL 100 and TIL 200, respectively, and 121 ETN partial responders/nonresponders switched to TIL 200 at week 28. Of TIL 100 or TIL 200 responders and ETN partial responders/nonresponders entering the extensions, 235/302, 176/213 and 85/107, respectively, were evaluated at week 244, and 88·7%, 92·5% and 81·3%, respectively, achieved PASI 75 response. Exposure‐adjusted rates of serious AEs were 6·3 and 6·0 patients with events per 100 patient‐years of TIL 100 and TIL 200, respectively. Conclusions: TIL treatment provided sustained disease control over 5 years in week 28 TIL responders and ETN partial responders/nonresponders, with a reassuring safety profile.